Effects of different levels of NaCl and CaCl2 on seed germination characteristics of Melissa officinalis L. and Ocimum basilicum L. - Mirmazloum, S. I.; Szabó, K.; PoorKalhor, V.; Németh, É. (International Journal of Horticultural Science, 2010)
More than 15 million hectares of Iran’s land areas are suffering from salinity.We investigated the effects of two types of salt (NaCl, CaCl2) in different levels on the germination and initial growth of two medicinal and aromatic plants, Melissa officinalis L. and Ocimum basilicum L. The experiment was carried out in Qazvin Agriculture and Natural Resource Research Center based on a randomized complete block design, for 14 days in a germinator. Sweet basil germinated above 50% in each saline treatment (EC=10 dSm-1), in alkali treatment (CaCl2=18800 mg/L) and in sodic-saline treatment (Ec=10 dSm-1; SAR=5.6), however at the highest concentrations germination was slowed down. Lemon balm showed a higher sensitivity: except the lowest NaCl treatment, each other ones inhibited germination and its rate to some extent. The combined treatments of both salts increased the stress reactions. However, seedling growth was less effected. The results showed a stimulating effect of NaCl treatment in 2500 mg/L (EC